Perceptions of substance use, treatment options and training needs among Iranian primary care physicians - Dolan Kate A; Day Carolyn; Nassirimanesh Bijan; Shakeshaft Anthony (BMC, 2005)
Abstract In order to be optimally effective, continuing training programmes for health-care professionals need to be tailored so that they target specific knowledge deficits, both in terms of topic content and appropriate intervention strategies. A first step in designing tailored treatment programmes is to identify the characteristics of the relevant health-care professional group, their current levels of content and treatment knowledge, the estimated prevalence of drug and alcohol problems among their patients and their preferred options for receiving continuing education and training. This study reports the results of a survey of 53 primary care physicians working in Iran. The majority were male, had a mean age of 44 years and saw approximately 94 patients per week. In terms of their patients' drug use, primary care physicians thought most patients with a substance use problem were male, women were most likely to use tobacco (52%), opium (32%) and marijuana/hashish and young people were most likely to use tobacco, alcohol, marijuana and heroin. Counselling and nicotine patches were the treatments most commonly provided. Although the majority (55%) reported referring patients to other services, more than a third did not. Most primary care physicians reported being interested in attending further training on substance abuse issues. The implications of these data for ongoing education and training of primary care physicians in Iran are discussed.